2018
DOI: 10.11604/pamj.2018.31.164.16477
|View full text |Cite
|
Sign up to set email alerts
|

Profil épidémio-clinique et évolutif des cardiomyopathies dilatées au Centre Hospitalier Universitaire de Brazzaville, Congo

Abstract: L'objectif de cette étude est de contribuer à l'amélioration de la prise en charge des patients porteurs de cardiomyopathies dilatées (CMD) à Brazzaville. Cette étude, prospective et analytique, a été réalisée au CHU de Brazzaville entre le 1 er Janvier 2014 et le 30 Juin 2015. Elle a inclus les patients hospitalisés dans le service de cardiologie pour une insuffisance cardiaque (IC) en rapport avec une CMD. L'étude a porté sur 100 patients. La fréquence hospitalière de la CMD était de 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The male predominance of this study is comparable to that of Stéphane Méo Ikama et al in Congo Brazzaville who had reported 55% of men [2]. The average age of our study is comparable to that of Aw F et al in Senegal in 2020 who noted an average age of 53.22 years [7].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The male predominance of this study is comparable to that of Stéphane Méo Ikama et al in Congo Brazzaville who had reported 55% of men [2]. The average age of our study is comparable to that of Aw F et al in Senegal in 2020 who noted an average age of 53.22 years [7].…”
Section: Discussionsupporting
confidence: 87%
“…Ambulatory Blood Pressure Measurement (ABPM), a no-invasive technique, is a method of measuring blood pressure (BP) which establishes a good correlation between the level of BP figures and target organ damage, the risk of cardiovascular disease, and the long-term prognosis of patients, unlike conventional clinical measurements [1]. This is an examination recommended for subjects at high cardiovascular risk, and those requiring a nocturnal drop in BP such as elderly and obese subjects, those with secondary or resistant hypertension, diabetics, subjects with metabolic syndrome or sleep apnea syndrome [1] [2]. In Sub-Sahara Africa, few works based on ABPM have been reported [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global initiatives for hypertension screening for an effective control are encouraged, and some initiatives have been undertaken [8] [9], including screening and prevention of RHD [4] [5] [10]. These diseases have various intra-hospital prognosis in Brazzaville due to various mortality causes according to several studies [3] [11].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazzaville, the prevalence of hypertension is 41% [8]. It is the leading cause of hospitalization in the department of cardiology, and the majority of patients are admitted for heart failure [3] [11].…”
Section: Introductionmentioning
confidence: 99%